Legal Review of Restrictions on Freedom of Expression on Social Media in the Context of State Security - Yordi Priambodo; Wieke Dewi Suryandari; Hono Sejati (Indonesian Journal Publisher, 2026)
The development of digital technology has brought significant changes in the way individuals express their opinions, particularly through social media. Freedom of expression is a fundamental right guaranteed by various national and international legal instruments. However, in practice, freedom of expression is not absolute and can be restricted for various reasons, one of which is state security. These restrictions often give rise to debates about the legitimate limits of regulation, particularly in the context of social media, which has a wide reach and rapid dissemination of information. This article aims to examine the legal aspects related to restrictions on freedom of expression on social media to maintain state security using normative juridical research methods. The normative juridical method in this research focuses on the analysis of laws and regulations, international legal instruments, and legal doctrines related to freedom of expression and state security. This study discusses the freedom of expression from a human rights perspective, and the legal principles underlying its restrictions, including the principle of proportionality, which emphasizes the balance between individual freedom and the public interest. The study analyzes national regulations governing freedom of expression on social media, such as the 1945 Constitution, the Electronic Information and Transactions Law (UU ITE), and various other regulations. These regulations are then compared with international legal standards, such as the International Covenant on Civil and Political Rights (ICCPR). The results are expected to provide a deeper understanding of how the law regulates restrictions on freedom of expression on social media, while evaluating the extent to which regulations in force in Indonesia align with human rights principles. This study recommends ensuring that restrictions on freedom of expression are implemented proportionately without compromising individuals' fundamental rights.